ICT-Linked Firm Reorganisation and Productivity Gains - Martin Falk (Austrian Institute of Economic Research (WIFO), 2004)
In the EU, most large firms use e-business applications, such as enterprise resource planning and online procurement. Based on e-business watch data for EU-4 (Germany, France, Italy and the United Kingdom) we find that the actual use of enterprise resource planning and online procurement is positively correlated with labour productivity growth. Furthermore, we find that certain e-business applications, such as Knowledge Management Solution (KMS) systems and CRM systems are significantly positively correlated to either sectoral skill intensity or information technology intensity. The results from the empirical analysis based on Community Innovation survey (CIS 3) data confirm the hypothesis that the introduction of business practices and new organisational practices are highly correlated. Furthermore, there is a significantly positive relationship between labour productivity growth and the percentage of enterprises with new or significantly changed organisational structures based on industry data for some EU countries.
Keywords: M20; L86; O31; O32; 330; organisational change; new business practices; economics of Information; Technology; Informationstechnik; E-Business; Produktivität; Organisation; Deutschland; Frankreich; Italien; Großbritannien